2020
DOI: 10.1186/s12879-020-05436-2
|View full text |Cite
|
Sign up to set email alerts
|

HIV knowledge and associated factors among young Ethiopians: application of multilevel order logistic regression using the 2016 EDHS

Abstract: Background Human Immunodeficiency virus continues to be a major global health problem infecting 75 million and killing 32 million people since the beginning of the epidemic. It badly hit Sub Saharan Africa than any country in the world and youths are sharing the greatest burden. The study aims to assess the level of HIV-knowledge and its determinants among Ethiopian youths using the 2016 Ethiopia Demographic and Health Survey data. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 34 publications
6
13
0
Order By: Relevance
“…Women residing in southern and central region were more likely to have comprehensive knowledge of HIV/AIDS compared to women residing in northern region. Our finding agrees with the results of studies conducted in Ethiopia and Uganda which also found variations in comprehensive knowledge of HIV/AIDS among women across the regions of these countries [ 31 , 32 ]. In Malawi, the majority of tertiary education institutions which host many students, mainly young women, are based in central and southern regions other than the northern region.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Women residing in southern and central region were more likely to have comprehensive knowledge of HIV/AIDS compared to women residing in northern region. Our finding agrees with the results of studies conducted in Ethiopia and Uganda which also found variations in comprehensive knowledge of HIV/AIDS among women across the regions of these countries [ 31 , 32 ]. In Malawi, the majority of tertiary education institutions which host many students, mainly young women, are based in central and southern regions other than the northern region.…”
Section: Discussionsupporting
confidence: 92%
“…In line with similar studies existing in the literature [ 24 , 31 ], the findings of this study show that comprehensive knowledge of HIV/AIDS was significantly correlated with ever been tested for HIV. Young women who ever tested for HIV were more likely to have comprehensive knowledge about HIV/AIDS compared to those who were not tested for HIV.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Supporting PLWH achieve positive effects in regard to their HRQOL requires understanding its determinants in this population. Studies have recognized a number of factors that are consistently associated with HRQOL among PLWH, including ageing, immunological status, the presence of symptoms, treatment adherence, depression, social support and employment [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…This may mean that attitudes toward PLHIV still plays a major role in explaining HIV testing inequalities regardless of the HIV epidemic in a country. HIV stigma has been well documented to be associated with higher SEP [29,30] and HIV testing uptake in the lifetime [30]. Stigma as an important mediator has implications for HIV testing.…”
Section: Discussionmentioning
confidence: 99%